RESPONSE OF POLLEN GERMINATION AND POLLEN TUBE GROWTH OF SOUR CHERRY GENOTYPES TO TEMPERATURE - Rakonjac, Vera; Čolić, Slavica; Marić, Slađana; Đorđević, Milena; Glišić, Ivana; Radičević, Sanja (Journal of Agricultural Sciences (Belgrade), 2026)
The aim of this study was to determine the influence of genotype, environmental factors across three consecutive years (2022–2024), and incubation temperature (17°C and 20°C) on in vitro pollen germination and pollen tube length in sour cherry, as well as to monitor flowering phenology during the same period. Six cherry genotypes were used: two cultivars created in the Republic of Serbia (“Sofija” and “Šumadinka”), one introduced cultivar (“Érdi Bötermö”), one autochthonous cultivar (“Feketićka”) and two promising genotypes (“GV-6” and “GV-10”). The flowering phenophase was recorded as the beginning, full and end of flowering. To determine germination and pollen tube length, pollen was collected and sown in Petri dishes on an agarose-sucrose nutrient medium and incubated at the two temperatures for 24 h. The obtained results demonstrated that flowering time varied between years in terms of date and duration. In vitro pollen germination ranged from 3.16% to 53.75%, while pollen tube length ranged from 225.6 μm to 960.2 μm. Significant differences were recorded between most sour cherry genotypes for both pollen germination and tube length. Differences between years were also significant, while incubation temperatures did not significantly affect the evaluated traits. The significant influence of many interactions, as established by analysis of variance, indicates that the response of genotypes to environmental conditions was different, which could be explained by differences in their stability. Knowledge of pollen germination and pollen tube growth plays a crucial role in understanding the value of a cultivar as a pollinator, both for commercial cultivation and breeding.